New trends in the treatment of androgenetic alopecia - Leonik, Szymon; Smoczok, Michał; Bergler-Czop, Beata (Dermatology Review/Przegląd Dermatologiczny, 2024)
Androgenetic alopecia is the most common form of non-cicatricial hair loss, affecting a significant proportion of the population, particularly men. Due to increasing societal demands for a flawless appearance, there is an increase in pressure on physicians and specialists to provide effective and safe treatment for patients suffering from androgenic alopecia. However, treatments with proven efficacy approved by recognised organisations and associations are limited, and research is ongoing to discover new drugs, redesign existing ones and establish therapy algorithms. This publication reviews the use of minoxidil, 5a-reductase inhibitors (applied orally, topically and by injection), tretinoin, botulinum toxin, microRNA, and osteopontin as treatment options for androgenetic alopecia in men.